2022
DOI: 10.3390/jcm11113002
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapies for the Treatment of Neuropathic Pain: Potential and Pitfalls

Abstract: Neuropathic pain affects more than one million people across the globe. The quality of life of people suffering from neuropathic pain has been considerably declining due to the unavailability of appropriate therapeutics. Currently, available treatment options can only treat patients symptomatically, but they are associated with severe adverse side effects and the development of tolerance over prolonged use. In the past decade, researchers were able to gain a better understanding of the mechanisms involved in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 176 publications
0
18
0
Order By: Relevance
“…While VGSCs play a crucial role in neuronal excitability and pain processing, alterations in these genes can only account for a portion of the complexity of PPN [7]. Recent studies have shown that other ICGs are involved in pain signaling, modulation, and transmission (Figure 1) [5,8,9]. This review delves into the growing function of ICGs in PPN, aside from VGSCs, which have been previously extensively discussed in recent reviews [7,10,11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While VGSCs play a crucial role in neuronal excitability and pain processing, alterations in these genes can only account for a portion of the complexity of PPN [7]. Recent studies have shown that other ICGs are involved in pain signaling, modulation, and transmission (Figure 1) [5,8,9]. This review delves into the growing function of ICGs in PPN, aside from VGSCs, which have been previously extensively discussed in recent reviews [7,10,11].…”
Section: Introductionmentioning
confidence: 91%
“…It is important to acknowledge that there is a correlation between pain perception and genetic variants in Ion Channel Genes (ICGs) [4]. As these ion channels play a critical role in generating, transmitting, and transforming nerve signals in the peripheral nerves, they must be thoroughly examined as promising molecular targets for PPN therapy [5]. Voltage-Gated Sodium Channels (VGSCs) are the most researched ICGs and have been linked to disorders such as congenital insensitivity to pain (CIP), paroxysmal extreme pain disorder (PEPD), erythromelalgia, small fiber neuropathy (SFN), and painful diabetic peripheral neuropathy (PDPN) [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are several associated problems that are manifested outside the challenges with pain. They include bowel 54 and urine problems, 59 palpitation (rapid heartbeats), 17 , 23 xerostomia (dry mouth), 60 keratoconjunctivitis sicca (dry eyes) 61 , and (hyperhidrosis) abnormal sweating. 54 Individuals with this condition suffer from orthostatic hypotension (when blood pressure drops suddenly upon standing) which can cause symptoms such as blurred vision, dizziness, and fainting.…”
Section: Small Fiber Neuropathymentioning
confidence: 99%
“…Reports show that good family functioning positively reduces negative emotions (Dang et al, 2021), improves functioning in daily activities (Signs & Woods, 2020), and improves the quality of life (Zhang et al, 2022). Nevertheless, due to the lack of evidence on the relationship between family factors and pain outcomes (Shinu et al, 2022), there is a need to understand these relationships in patients with NP to provide ideas for their pain management.…”
Section: Introductionmentioning
confidence: 99%